Menguatkan Kompetensi Guru SD dalam Bimbingan dan Konseling - Ima Ni'mah Chudari; Firman Robiansyah; Ajo Sutarjo; Darmawan Darmawan (Universitas Pendidikan Indonesia Kampus Serang, 2021)
Class teachers are the closest and most intense parties in daily communication with students. In their duties and obligations as organizers, they are required to be able to create situations, lead, stimulate and move and direct teaching and learning activities. In addition, teachers must be parents of their students. Class teachers in elementary schools must prepare themselves and strengthen their competence in the science of Guidance and Counseling (GC) services. Community service activities in the form of workshops or workshops for classroom teachers in elementary schools, aim to provide practical knowledge and skills in student guidance service activities in elementary schools. This community service program activity is carried out in the form of a workshop or workshop, which consists of theoretical presentations and training in the preparation of GC work programs for elementary schools. The target audience were teachers and principals of Teaching Laboratory Elementary School -UPI Campus in Serang and teachers of State Elementary School of Tembong Serang, totaling 9 people. The results of this community service activity are: (a). understanding of the objectives and principles of guidance services in SD; (b) in understanding about the work program of guidance services in elementary schools; (c) teachers can practice how to make work programs for guidance services in elementary schools; (d) encourage teachers to carry out guidance service activities in elementary schools. The hope of this program is to create an ecosystem and improve the quality of guidance by classroom teachers in targeted primary schools.